Changes in Right Ventricular Volume, Volume Load, and Function Measured with Cardiac Computed Tomography over the Entire Time Course of Tetralogy of Fallot - Goo, Hyun Woo (Korean J Radiol, 2019)
OBJECTIVE: To characterize the changes in right ventricular (RV) volume, volume load, and function measured with cardiac computed tomography (CT) over the entire time course of tetralogy of Fallot (TOF). MATERIALS AND METHODS: In 374 patients with TOF, the ventricular volume, ventricular function, and RV volume load were measured with cardiac CT preoperatively (stage 1), after palliative operation (stage 2), after total surgical repair (stage 3), or after pulmonary valve replacement (PVR) (stage 4). The CT-measured variables were compared among the four stages. After total surgical repair, the postoperative duration (POD) and the CT-measured variables were correlated with each other. In addition, the demographic and CT-measured variables in the early postoperative groups were compared with those in the late postoperative and the preoperative group. RESULTS: Significantly different CT-based measures were found between stages 1 and 3 (indexed RV end-diastolic volume [EDV], 63.6 ± 15.2 mL/m(2) vs. 147.0 ± 38.5 mL/m(2) and indexed stroke volume (SV) difference, 7.7 ± 10.3 mL/m(2) vs. 32.2 ± 16.4 mL/m(2); p < 0.001), and between stages 2 and 3 (indexed RV EDV, 72.4 ± 19.7 mL/m(2) vs. 147.0 ± 38.5 mL/m(2) and indexed SV difference, 5.7 ± 13.1 mL/m(2) vs. 32.2 ± 16.4 mL/m(2); p < 0.001). After PVR, the effect of RV volume load (i.e., indexed SV difference) was reduced from 32.2 mL/m(2) to 1.7 mL/m(2). Positive (0.2 to 0.8) or negative (−0.2 to −0.4) correlations were found among the CT-based measures except between the RV ejection fraction (EF) and the RV volume load parameters. With increasing POD, an early rapid increase was followed by a slow increase and a plateau in the indexed ventricular volumes and the RV volume load parameters. Compared with the preoperative data, larger ventricular volumes and lower EFs were observed in the early postoperative period. CONCLUSION: Cardiac CT can be used to characterize RV volume, volume load, and function over the entire time course of TOF.